IFPRI's strategy at a glance: toward food and nutrition security - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
This paper sets out the strategy for the International Food Policy Research Institute (IFPRI) for the next decade. A new look at IFPRI’s strategy is timely because hunger and malnutrition in the developing world remain persistently high. Also, the policy environment in which IFPRI operates is changing: central government authority in making food policy is becoming more diffuse, with many more actors involved. Furthermore, new technologies offer great promise for advancing food security, but research is needed to identify policies and institutions to ensure that food-insecure people have access to adequate food and nutrition. At the same time, global health crises pose significant threats to food security and nutrition. Finally, the agenda built on the Millennium Development Goals (MDGs) calls for IFPRI’s contribution.